Quality, not just quantity: lessons learned from HIV testing in Salvador, Brazil - MacCarthy, Sarah (2014)
Studies have demonstrated that an early HIV diagnosis is a critical first step towards continued engagement in care. We examined HIV testing experiences in Salvador, Brazil, to understand how a focus on quality services can inform service provision more generally in the post-2015 global health agenda. Seventeen semi-structured interviews were conducted with HIV-positive pregnant women in Salvador, a large urban centre of north-east Brazil. Interviews were transcribed, translated and coded for analysis. Deductive codes confirmed factors identified in the literature review. Inductive codes highlighted new factors emerging from the initial coding. 'Quality' was defined according to global and national guidelines as HIV testing with informed and voluntary consent, counselling and confidentiality (3Cs). No pregnant woman experienced all elements of the 3Cs. Three women did not experience any informed and voluntary consent, counselling or confidentiality. Few women provided consent overall and none received pre-test counselling. Post-test counselling and confidentiality of services were more consistently provided. This study suggests that testing in Salvador - the third-largest city in the country - is not of the quality called for by global and national guidelines, despite the fact that HIV testing is being routinely provided for HIV-positive pregnant women in Brazil. Going forward, additional clarity around the 3Cs is necessary to improve how the quality, not just the quantity, of HIV services is measured.